2001
DOI: 10.1016/s0738-3991(00)00201-9
|View full text |Cite
|
Sign up to set email alerts
|

Cure-oriented versus care-oriented attitudes in medicine

Abstract: This article focuses on the attitudinal component of patient-centredness. The literature reveals that the relationship between cure-and care-oriented attitudes remains to be clari®ed. The aim of this study is to gain further insight in the relationship between cure and care attitudes by questioning the bipolar unidimensional structure of the concept. By means of an empirical analysis among Belgian medical students, the cure versus care attitudes regarding the`ideal physician' are investigated. Traits of the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 19 publications
1
50
0
6
Order By: Relevance
“…In 2001 de Valck [4] presented a questionnaire measuring students' attitudes towards full disclosure versus non-disclosure in breaking bad news. Following one cohort of students for three years (53 students responded in all three years) they found that students became more in favour of non-disclosure as they progressed through medical school.…”
Section: Introductionmentioning
confidence: 99%
“…In 2001 de Valck [4] presented a questionnaire measuring students' attitudes towards full disclosure versus non-disclosure in breaking bad news. Following one cohort of students for three years (53 students responded in all three years) they found that students became more in favour of non-disclosure as they progressed through medical school.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps we can learn from the female students, who were reported by, for example, Batenburg et al (1999) and De Valck et al (2001) to be more attuned to care-oriented attitudes. This may be related to Western culture being more accepting of women discussing feelings as opposed to men (Tsimtsiou et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the three-factor solution that we found and the moderate correlations of the factors suggest that the students may see the ideal doctor as someone who can be characterised as care oriented on a rational versus emotional dimension, but also as cure oriented on a biomedical versus psychosocial dimension or any other combination. The implication of this view would be that a care orientation and a cure orientation are not necessarily mutually exclusive but, instead, the two can go together and such a combined orientation may even be a characteristic of doctors that are well equipped to deal with the current and future needs of patients (Batenburg et al 1999;De Valck et al 2001). In addition to educational innovation aimed at fostering care orientations in future doctors, the chronically ill patients are likely to be best served also by appropriate health care innovations, such as the use of physician assistants and nurse practitioners, and trying to find more effective ways of communication between health-care workers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations